Selectively sparing the submandibular gland when level Ib lymph nodes are included in the radiation target volume: An initial safety analysis of a novel planning objective. (February 2019) - Varra, Vamsi; Ross, Richard B.; Juloori, Aditya; Campbell, Shauna; Tom, Martin C.; Joshi, Nikhil P.; Woody, Neil M.; Ward, Matthew C.; Xia, Ping; Koyfman, Shlomo A.; Greskovich, John F.
Highlights: Sparing of the SMG when targeting the level Ib nodes was feasible. Sparing of the SMG reduced mean dose to the SMG. Sparing of the SMG did not result in increased level 1b nodal failure rates. Abstract: Background: Submandibular gland (SMG) metastases are extremely rare in head and neck cancer, even in the presence of level Ib lymph node (LN) involvement. In recent years, we have contoured the SMG and specifically attempted to limit its dose exposure even in patients in whom the level Ib LN station is targeted. This study reports our preliminary feasibility and safety experience with selective submandibular gland sparing. Methods: Patients with squamous cell cancer (SCC) of the oral cavity or oropharynx with T1-2, N0-3, M0 disease in whom at least a single level Ib lymph node region was included in the target volume were identified. All patients were treated from 2009 to 2014 with definitive or postoperative IMRT with or without chemotherapy. Patients with recurrent disease, previous radiation or treated palliatively were excluded. Results: A total of 174 patients met criteria for inclusion. Among the 185 level Ib LN stations that were deliberately targeted in the clinical treatment volume, 32 submandibular glands were contoured, excluded from the target volume and avoided during treatment planning. Mean dose to the spared SMG were reduced by 12% (66.6 Gy vs. 58.9 Gy, p < .001). None of these patients experienced any level 1b LN failures. Conclusion: Selective sparing of the submandibular gland when targeting the level 1b nodes in oral cavity and oropharynx cancer is feasible, reduces the mean dose to submandibular glands and does not result in increased level 1b nodal failure rates. Additional studies with larger cohorts are needed to validate this preliminary observation.